Inhomogeneous rear reflector induced hot-spot risk and power loss in building-integrated bifacial c-Si photovoltaic modules. (January 2021) - Kim, Chungil; Jeong, Myeong Sang; Ko, Jaehwan; Ko, MyeongGeun; Kang, Min Gu; Song, Hyung-Jun
Abstract: A building-integrated bifacial photovoltaic (BF-PV) module is a strong candidate for realizing zero-energy buildings because it can achieve high power output by collecting light from both the front and rear sides of the building. However, harvesting non-uniformly distributed rear incident light is a very challenge issue in BF-PV. In this study, we empirically investigated the effect of an inhomogeneous rear surface on the power and reliability of a BF-PV. The mini-module test showed that a non-uniform rear reflection triggers a current mismatch among cells, resulting in the overheating of cells above the low reflectance surface. In particular, a large difference in the reflectance inside the rear reflector installed close to the module increases a hot-spot risk. This risk can be reduced by minimizing the variation of the reflectance, as well as elongating the distance between the cell and the reflector. A theoretical calculation based on empirical results indicated that an inhomogeneous rear reflector results in power loss or a reliability issue in BF-PV modules. Hence, the rear surface of a BF-PV module should be carefully designed or considered in order to maximize its performance and reliability. Highlights: Rear surface position and reflectance affect bifacial photovoltaic module performance. Inhomogeneous rear reflectors cause current mismatches among cells and local heating. Inhomogeneous rear reflectors lead to power losses and reliability issues.